In search of the origins of the Malay-Muslim architectural heritage through masjid built form - Mohd Nawawi, Norwina; Abdul Majid, Noor Hanita (IIUM Press, 2011)
Teaching of architectural history to students of architecture leaves so many gaps to the rationale of its claim with no appropriate answer on the Malay-Muslim heritage in the South East Asian region. The similarities found in the architectural styles of the so called "The Malay Archipelago" had triggered many theories among architectural writers, historian and critics. Understanding the development of civilisation in the said region that is connected to the architectural establishment in both styles and typologies is important. For the purpose of this article, the study intends to discuss selected theories and review some examples of architectural forms of Masjid as the key architectural building of the Malay world found in Thailand, Indonesia, Malaysia, Cambodia, Laos PDR and Vietnam. Qualitative approach through literature reviev,l and observational visits to selected case studies, where available, were conducted. Preliminary fmdings from the analyses of case studies suggest that understanding the similarities and differences of the architectural forms could explain the origins ofthe Malay-Muslim heritage, insh'aallah.